1983
DOI: 10.2136/sssaj1983.03615995004700040007x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidation of Arsenite by Various Manganese Dioxides

Abstract: Three Mn dioxides—birnessite, cryptomelane, and pyrolusite—were examined for their ability to deplete the concentration of As(III), a highly toxic pollutant, in solution. The depletion [oxidation of As(III) to As(V) and sorption of As(III)] of As(III) by all three Mn dioxides follows first‐order kinetics. The rate constants for the depletion of As(III) by birnessite and cryptomelane at 298 K are 0.267 and 0.189 h−1, respectively. On the other hand, the depletion rate of As(III) by pyrolusite is much slower: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 0 publications
7
143
2
Order By: Relevance
“…Mn oxides are common soil minerals with a high capacity to oxidize heavy metals and metalloids including As(III) (Post 1999). The effective oxidation of As (III) by synthetic Mn oxides such as birnessite (δ-MnO 2 ) has been reported (Oscarson et al 1981(Oscarson et al , 1983. However, 4…”
Section: Solid Phase Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Mn oxides are common soil minerals with a high capacity to oxidize heavy metals and metalloids including As(III) (Post 1999). The effective oxidation of As (III) by synthetic Mn oxides such as birnessite (δ-MnO 2 ) has been reported (Oscarson et al 1981(Oscarson et al , 1983. However, 4…”
Section: Solid Phase Analysismentioning
confidence: 99%
“…Although As(III) specifically adsorbs to iron (hydr)oxides (Dixit and Hering 2003), it is generally accepted that ferric iron [Fe(III)] in soils does not oxidize As(III) significantly. Manganese oxide minerals (Mn oxides) are another important minerals, since they readily oxidize As(III) to As(V) (Oscarson et al 1983). Although Mnoxides are effective oxidants, the rate of As(III) oxidation decreases with time due to blocking of surface reactive sites by reaction products such as As(V), Mn(II) and possibly Mn(III) (Lafferty et al 2010a(Lafferty et al , 2010b.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation was designed to link the findings of previous work (18)(19)(20)(21) with new information derived from EXAFS spectroscopy.…”
Section: +mentioning
confidence: 99%
“…Oscarson et al [27] found that the oxidation of As(III) by birnessite, cryptomelane, and pyrolusite obeyed the first-order rate law with the rate constants at 298 K being 0.267, 0.189 and 0.44 × 10…”
mentioning
confidence: 99%
“…However, Chen and Fang [28] reported that the oxidation rate of As(III) by MnO 2 was rapid initially followed by a firstorder kinetics with respect to As(III) concentration. The activation energies for the oxidation reaction by the MnO 2 were measured to be in the range 26.0 -32.3 kJ/mol [27]. The oxidation process was reported to be limited by diffusion of the reactant As(III) to or the reaction products away from the surface [27][28][29].…”
mentioning
confidence: 99%